1962
DOI: 10.1126/science.136.3512.264
|View full text |Cite
|
Sign up to set email alerts
|

Peach Mesocarp Explant Enlargement and Callus Production in vitro

Abstract: Explants from fruits of the peach were stimulated to grow by cell enlargement, cell division, or both when placed on media containing kinetin. Callus cultures have been obtained, even occasionally from ripening fruits, long after cessation of normal cell division.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1965
1965
1981
1981

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…This suggested the presence of unidentified growth-promotive substances in these additives. Support for this view was the finding that kinetin produced a similar response to coconut milk in promoting cell division in cultured tissues [6,7,20]. Extensive research resulted in the identification of a number of cytokinins in both coconut milk [10,24] and malt extract [25].…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…This suggested the presence of unidentified growth-promotive substances in these additives. Support for this view was the finding that kinetin produced a similar response to coconut milk in promoting cell division in cultured tissues [6,7,20]. Extensive research resulted in the identification of a number of cytokinins in both coconut milk [10,24] and malt extract [25].…”
Section: Introductionmentioning
confidence: 84%
“…Coconut milk, the liquid endosperm of the fruit of Cocos nucifera k., and malt extract, processed from germinating barley grains, are widely used as additives in plant tissue culture experiments [2,6,7,13,14,20,23]. Although tire chemical composition of these additives has been studied extensively [15,22], the use of individual or combinations of the isolated components has not produced as favourable results as were obtained with complete coconut milk and malt extract [6,14].…”
Section: Introductionmentioning
confidence: 99%
“…From autoclaved herring sperm DNA a cell-division-inducing substance was isolated, which due to its specific effect on cytokinesis, was named kinetin (11). Subsequent experiments showed that CM can substitute for kinetin in supporting the growth of plant tissues in culture (5,16), suggesting that kinetin-like substances are present in it. The isolation of a number of purine-type substances, from CM which showed kinetinlike activity in delaying leaf senescence (15), supported this contention.…”
Section: Introductionmentioning
confidence: 99%
“…Expiants of developing soybean pod tissue from several Glycine species also formed callus and roots when grown in vitro. The develop ment of callus from mature fruit tissue cultures is not uncommon and has been described in citrus and non-citrus species (Schroeder and Spector, 1957;Letham, 1958;Sommer et al, 1962), and rhizogenesis has been described in avocado cultures (Schroeder et al, 1962).…”
Section: Tissue In Culturementioning
confidence: 99%